Fermentation of glucose-1-phosphate: a screening test for fermentative Bacteroides species. - Wilkins, T D (1976)
Of 1,504 strains of anaerobic bacteria tested, 544 produced acid from glucose-1-phosphate. Of these, 535 were fermentative strains of Bacteroides; only three fermentative Bacteroides strains were negative. The reaction may be useful for determination of the number of Bacteroides species present in colon content and feces.